Criminal justice and criminology research methods - Kraska, Peter B. (Pearson/Allyn & Bacon, 2008)
Crime and justice research : mapping the terrain -- The nature of science and research -- Philosophical and theoretical foundations -- Ethics and reviewing the literature -- Quantitative and qualitative research design -- Quantitative and qualitative measurement -- Quantitative and qualitative sampling -- Experimental and quasi-experimental crime and justice research -- Survey interview methods -- Nonreactive research : content analysis and existing documents/statistics -- Analysis of quantitative data -- Crime and justice ethnographic field research -- Historical, ethnographical content analysis, legal and mixed methods -- Analysis of qualitative data -- Presenting crime and justice research